Cascade use of wood in the Czech Republic - Babuka, Róbert; Sujová, Andrea; Kupčák, Václav (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2020)
Research Highlights: One of the priorities of the European Commission is to build up an effective circular economy based on recycling and multiple use of materials. Wood biomass is a renewable raw material and can be used several times in a cascading sequence. Each country has a unique situation regarding the availability and utilization of wood sources. Background and Objectives: The objective of this study was to analyze wood flow in the Czech Republic using the cascading principle of biomass use. The specific situation in the Czech Republic lies in a lack of valid and reliable input data from official statistics. Therefore, the reverse input method was applied. Materials and Methods: Input data analyses of roundwood sources and foreign trade were based on official statistical data. The calculation of raw wood volume consumption in primary processing was performed based on the data after our own correction and recalculation. It was then possible to build up a basic model of multi-stage cascade wood use. The input volume of roundwood was divided among all types of primary processing production using conversion factors. Results: Cascading use of wood (CUW) showed the level of efficiency of the resource. Official statistical input data and the reversed input data regarding raw wood volume entering wood processing revealed differences at a level of 27%. The overall CUW in the Czech Republic indicates a high rate of wood use in primary processing with low added value and in generating energy. Conclusions: The reverse input method reveals the real situation of wood consumption irrespective of the level of official statistical data. It is suitable to apply in an environment of incomplete or incorrect input data. CUW in Czechia showed an opportunity for increasing the efficiency of wood utilization. The structure of wood use needs to be optimized towards creating greater added value.
Keywords: Cascade use; Forest-based sector; Reverse input method; Wood flow